Thread integrated smart-phone imaging facilitates early turning point colorimetric assay for microbes. Issue 45 (17th July 2020) - Prabhu, Anusha; Nandagopal M. S., Giri; Peralam Yegneswaran, Prakash; Prabhu, Vijendra; Verma, Ujjwal; Mani, Naresh Kumar
Abstract : A proof-of-concept unifying thread devices and smart-phone imaging for low-cost microbial detection based on simple colour change. Abstract : This study employs a commercial multifilament cotton thread as a low-cost microbial identification assay integrated with smartphone-based imaging for high throughput and rapid detection of pathogens. The thread device with inter-twined fibers was drop-cast with test media and a pH indicator. The target pathogens scavenge the media components with different sugars and release acidic by-products, which in turn act as markers for pH-based color change. The developed thread-based proof-of-concept was demonstrated for the visual color detection (red to yellow) of Candida albicans (≈16 hours) and Escherichia coli (≈5 hours). Besides that, using a smart-phone to capture images of the thread-based colorimetric assay facilitates early detection of turning point of the pH-based color change and further reduces the detection time of pathogens viz. Candida albicans (≈10 hours) and Escherichia coli (≈1.5 hours). The reported thread and smartphone integrated image analysis works towards identifying the turning point of the colorimetric change rather than the end-point analysis. Using this approach, the interpretation time can be significantly reduced compared to the existing conventional microbial methods (≈24 hours). The thread-based colorimetric microbial assay represents a ready-to-use, low-cost and straightforward technology with applicability in resource-constrained environments, surpassing the need for frequent fresh media preparation, expensive instrumentation, complex fabrication techniques and expert intervention. The proposed method possesses high scalability and reproducibility, which can be further extended to bio(chemical) assays.